Peningkatan Pengetahuan Petugas Administrasi Tentang Sistem Informasi Manajemen Rumah Sakit (SIMRS) - Rusnita, Rusnita; Pramono, Edi; Kamaruddin, Muh. Ihsan; Nashrulloh, Dewi; Tenriawi, Westy (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2025)
The Hospital Management Information System (SIMRS) is a crucial component in supporting the efficiency and effectiveness of healthcare services in hospitals. However, limited understanding of SIMRS among administrative staff often hinders its optimal implementation. This Community Service (PKM) activity aims to improve the knowledge and skills of administrative staff at Hospital X through training and mentoring related to the use and management of SIMRS. The methods used included counseling, simulations, and pre- and post-test evaluations. The results of the activity showed a significant increase in participants' understanding and skills regarding SIMRS features. This activity is expected to improve the overall quality of documentation and hospital administration services.